How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmeda, Rukhsana; et al. (Science Direct, 2022)
This article was published in the Social Science and Medicine [© 2018 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/BY/4.0/).] and the definite version is available at : https://doi.org/10.1016/j.socscimed.2018.05.002 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S0277953618302375